Digital Smart Branch Innovation: Increase Customer Satisfaction and Loyalty Through Quality Service - Gusti Ayu Ita Purnami; I Gede Sanica (UNIVED Press, 2024)
The development of the situation and business conditions of the banking industry in the future will be more competitive. Therefore, the banking world is required to show better performance to create synergy and provide high value to customers so that it can result in customer loyalty to the bank and is the main key for banks to be able to compete with other banks. The purpose of this study is to re-analyze the effect of digitalization of smart branch services, and service quality, on customer loyalty with customer satisfaction as a mediation variable. The method used in determining the number of samples in this study is non-probability sampling. After all, the population of researchers is not limited or unclear, to save work time, energy, and costs because the population of researchers is limited to the category of researchers. Respondents in this study were 80 0rg. The data was analyzed using the Partial Least Squares (PLS) Technique. The results of this study show that digitalization of smart branch services has a negative and insignificant effect on customer loyalty but has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction and customer loyalty, and customer satisfaction can mediate the influence of digitization of service and service quality on customer loyalty. The results of this study can be used as a reference for increasing Bank Mandiri customer loyalty